Le due vie weberiane del patrimonialismo. Potere personale e reti politiche - Brancaccio, Luciano (SocietàMutamentoPolitica, 2023)
Weberian categories provide a wide array of tools for understanding the phenomenon of political clientelism. They are useful not only for classifying forms, behaviors, and relationships, but also, from a diachronic and processual perspective, for comprehending the transformations affecting personalistic systems. Starting with the distinction between bureaucratic neo-patrimonialism and ceto-patrimonialism, this essay presents some theories and interpretative models that are useful for investigating even the more recent forms in which monocratic-type of personal power and political networks based on circuits of resource exchange are manifested.